2012
DOI: 10.1002/prep.201100033
|View full text |Cite
|
Sign up to set email alerts
|

Diaminofuroxan: Synthetic Approaches and Computer‐Aided Study of Thermodynamic Stability

Abstract: Different approaches to synthesize diaminofuroxan are presented herein. Mathematical and quantum chemical methods were used to study the possible reasons for failures in the syntheses of diaminofuroxan. Additionally, structural isomers of this compound were generated. With the help of the results of quantum chemical calculations at levels of DFT B3LYP 6‐31G(d) and MP2 6‐31G(d), screening of the most stable isomeric forms in the gaseous phase and in water was performed. It was shown that diaminofuroxan is not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The small adiabatic energy gap increases the strength of the non-adiabatic coupling of the surfaces and the probability of a non-adiabatic transition from the upper to lower electronic states. As the molecule evolves from the S 1 to S 0 state through (S 1 /S 0 ) CI(1)-(3) , the IRC algorithm shows that the steepest descent pathway for the molecule is to evolve to stable intermediate states S 0,im(1)(2) along reaction paths (1) and (2) or to the stable Franck-Condon structure S 0,FC along reaction path (3). From the IRC scan through reaction paths (1) and (2), the furoxan ring remains open at the intermediate states S 0,IM(1)(2) following (S 1 /S 0 ) CI(1) (2) .…”
Section: Fig 7 Structures Of All Critical Points and Conical Intersmentioning
confidence: 99%
See 2 more Smart Citations
“…The small adiabatic energy gap increases the strength of the non-adiabatic coupling of the surfaces and the probability of a non-adiabatic transition from the upper to lower electronic states. As the molecule evolves from the S 1 to S 0 state through (S 1 /S 0 ) CI(1)-(3) , the IRC algorithm shows that the steepest descent pathway for the molecule is to evolve to stable intermediate states S 0,im(1)(2) along reaction paths (1) and (2) or to the stable Franck-Condon structure S 0,FC along reaction path (3). From the IRC scan through reaction paths (1) and (2), the furoxan ring remains open at the intermediate states S 0,IM(1)(2) following (S 1 /S 0 ) CI(1) (2) .…”
Section: Fig 7 Structures Of All Critical Points and Conical Intersmentioning
confidence: 99%
“…1 The furoxan ring, containing an active oxygen atom in the ring, which forms a veiled nitro group in combination with an N-oxide fragment, is a useful building block in the synthesis of energetic materials with nitrogen containing heterocycles. 1,2 The structure of furoxan ring is shown in Figure 1; it is characterized as an electron rich system, with a pronounced withdrawal of electronic charge by the O atom of the Noxide moiety (exocyclic O atom). [3][4][5] The N− −O bond of the exocyclic N− −oxide moiety is reported to be as short as an actual double bond, while the endocyclic N− −O bond is longer than a typical single bond for this moiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above-mentioned integration strategy, 3,4-diaminofurazan (1), as a nucleophile and a known important precursor for synthesizing new EMs [10][11][12][13], and three chlorinated nitrated benzene derivatives [1-chloro-2,4-dinitrobenzene (2), 1-chloro-2,4,6-trinitrobenzene (3) and 4-chloro-7-nitro-2,1,3-benzoxadiazole (4)] which can provide points of attacks for nucleophiles were chosen as raw materials to synthesize new insensitive high-energy compounds with high thermal stability. As a result, four energetic ring-substituted furazans [3-amino-4-(2,4-dinitroanilino)furazan (5), 3-amino-4-picrylaminofurazan (6), 3,4bis(picrylamino)furazan (7) and 4-(4-aminofurazanamino)-7nitro-2,1,3-benzoxadiazole (8)] were synthesized through the above aromatic nucleophilic substitution system.…”
Section: Introductionmentioning
confidence: 99%
“…
1Introduction 1,2,5-Oxadiazole (furazan)a nd its 2-oxides( furoxan) represent au nique type of heterocyclic compounds and have been vigorously studied in the last decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14].A so ne of the most simple furazan ring compounds, 3,4-diaminofurazan (DAF) was first synthesized by Coburn in 1968 [15]. DAF is av ery simple high-nitrogenc ompound (56.0 %), and presents good properties [16].B ecause of two strong active adjacent aminog roups in its molecule,D AF has been considered as basic structure to prepare other complicated energetic compoundsb yo xidation, acylation and azidationr eaction. An umber of energetic compounds base on DAF,s uch as aminonitrofurazan (ANF), 3,4-dinitrofurazan (DNF), 4,4-diamino-3,3-azoxyfurazan( DAAF) and 4,4-diamino-3,3-azofurazan (DAAzF), have been reported in recent years [17][18][19][20][21][22][23][24][25],a nd the subsequent studiess howed that DAF-based energetic materials have excellent properties [26,27].Nevertheless, the thermalb ehavior of DAF was investigated rarely.S ome experimental results have shown that DAF and other furazan ring compoundsp ossess certain volatility after melting.
…”
mentioning
confidence: 99%